A Conceptual Framework for Incorporating Human Dimensions Into Integrated Ecosystem Assessments - Szymkowiak, Marysia (Frontiers in Marine Science, 2021)
The evolution of fisheries science and management towards an ecosystem perspective necessitates the meaningful incorporation of human dimensions. Whereas great strides have been made over the last several decades at moving towards ecosystem based fisheries management (EBFM), largely through the development of integrated ecosystem assessments (IEAs), the inclusion of human dimensions into these efforts has often been fragmentary and, in juxtaposition to the biophysical dynamics, sometimes even seemingly superficial. This presents a great challenge to the accuracy and applicability of these results, as the lack of appropriate incorporation of humans can be problematic in terms of both social and biophysical consequences. This study systematically documents current social science understanding of the multiple human dimensions that should be incorporated within ecosystem assessments and the overall approach to each of these within IEAs and other EBFM efforts. These dimensions include the multi-faceted nature of human well-being, heterogeneity in human well-being derived from fisheries, adaptive behaviors, and cumulative effects. The systematic inclusion of these dimensions into IEAs is then laid out in a conceptual framework, which is supplemented with a data collection scheme that is intended to facilitate operationalization. The detailed examination of incorporating human dimensions within IEAs presented in this study should further resonate with other ecosystem assessment efforts, providing not just ample evidence of the need for moving beyond simplistic assumptions of human homogeneity but a means of systematically integrating a more realistic and representative perspective.